1996
DOI: 10.1021/bi9600761
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel α-Neurotoxins Isolated from the Taipan Snake, Oxyuranus scutellatus, Exhibit Reduced Affinity for Nicotinic Acetylcholine Receptors in Brain and Skeletal Muscle

Abstract: Three novel toxic peptides were purified to homogeneity from the venom of the Australian taipan snake, Oxyuranus scutellatus scutellatus. On the basis of complete amino acid sequence analyses, two of these toxins belong to the family of short-chain alpha-neurotoxins found in elapid and hydrophid snake venoms and are the first postsynaptic neurotoxins identified in taipan venom. Radioligand binding studies confirm that taipan toxins 1 and 2 inhibit the binding of [125I]-alpha-bungarotoxin to nicotinic acetylcho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
2
27
0
1
Order By: Relevance
“…This is in sharp contrast with the Torpedo receptor, which recognizes with high affinities both short chain and long chain curaremimetic toxins from snake venoms. A differential selectivity between long chain and short chain toxins has been depicted previously toward the chick optic lobe (34), suggesting that our observations, made with a recombinant ␣7 receptor, may also occur in vivo. However, for this extrapolation to be valid, one needs to demonstrate that the recombinant chimeric receptor behaves just like the natural ␣7 receptor toward the toxins.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is in sharp contrast with the Torpedo receptor, which recognizes with high affinities both short chain and long chain curaremimetic toxins from snake venoms. A differential selectivity between long chain and short chain toxins has been depicted previously toward the chick optic lobe (34), suggesting that our observations, made with a recombinant ␣7 receptor, may also occur in vivo. However, for this extrapolation to be valid, one needs to demonstrate that the recombinant chimeric receptor behaves just like the natural ␣7 receptor toward the toxins.…”
Section: Discussionsupporting
confidence: 77%
“…Recently, it was observed that ␣-Bgtx and two new short chain toxins from the Australian snake Oxyuranus scutellatus bind to homogenates from chick optic lobes, a tissue that is likely to contain various neuronal receptors, including the ␣7 receptor. How- ever, only the long chain toxin, ␣-Bgtx, binds to the homogenate with high affinity (34).…”
Section: Production and Characterization Of The Chimeric ␣7 Achr-mentioning
confidence: 99%
“…We described here the identification of a neurotoxin from the venom gland cDNA library of O. scutellatus, and its further characterisation by 5RACE and cloning. The transcript was identified as a short-chain neurotoxin which was previously described at the mature protein level from the venom of the coastal taipan [19]. Subsequent PCR amplification identified a related family of toxins within the venom glands of eight other Australian elapids, including the short neurotoxin Pa-a from P. australis, which shares 72.6% identity at the protein level (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…The mature protein sequence of Os SNTX-1, excluding propeptide, had previously been determined by Zamudio et al [19], who described the isolation and characterisation of two toxins, toxins 1 and 2, from the venom of the coastal taipan which differed by only a single residue. Primers were designed from Os SNTX-1 to identify related neurotoxins in the venom gland of other Australian elapid snakes by PCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation